Tumor Regression Grade Predicts Survival in Locally Advanced Gastric Adenocarcinoma Patients with Lymph Node Metastasis - Yilin Tong; Yanmei Zhu; Yan Zhao; Zexing Shan; Jianjun Zhang; Dong Liu (Gastroenterology Research and Practice)
Background. Tumor regression grade (TRG) is widely used in gastrointestinal carcinoma to evaluate pathological responses to neoadjuvant chemotherapy (NCT), but whether it is an independent prognostic factor is still controversial. The aim of this study is to investigate the value of TRG in locally advanced gastric adenocarcinoma patients who underwent NCT and curative resection. Methods. Pathological regression was reevaluated according to the Mandard TRG. Survival curves were obtained by the Kaplan–Meier method, and differences in overall survival (OS) and disease-free survival (DFS) were compared using the log-rank test. Univariate and multivariate analyses for survival were based on the Cox proportional hazards method. Results. In total, 290 patients were identified in our electronic database. In univariable analysis, TRG was associated with OS (HR=3.822, P≤0.001) and DFS (HR=3.374, P≤0.001). However, in multivariable analysis, TRG was not an independent factor for OS (P=0.231) or DFS (P=0.191). In the stratified analysis, TRG retrieved prognostic significance in patients with the metastasis of lymph node (HR=2.034, P=0.035 for OS; HR=2.220, P=0.016 for DFS), while not in patients with negative lymph node (P=0.296 for OS; P=0.172 for DFS). Conclusions. TRG was not an independent predictor for survival, but the system regained its predicting significance in patients with lymph node metastasis.